Immobilization of Candida rugosa lipase on grafted-PGMA polymer for industrial applications - Binti Akbar Tajudin, Hazimah; Mirghani, Mohamed Elwathig Saeed; Al-Khatib, Ma An Fahmi Rashid; Mohd. Salleh, Hamzah (2017)
Lipases are among the most used enzymes in both hydrolysis and formation of ester bond between glycerol and fatty acids. However, free enzymes limit its long usage in term of its reusability, downstream separation and instability. The high demand on the use of lipases in industry urge the alteration of these soluble enzymes. Radiation- induced graft polymerization is one of the methods to introduce functional groups into polymer. Poly(glycidyl methacrylate) was being introduced onto non-woven polyethylene/polypropylene sheet introducing a reactive epoxide group which is able to react with other functional groups forming stable covalent bonds without any linkers.